The experienced condition and moderating variables as a potential predictor of visitor thresholds in outdoor recreation settings - Doeblin, Dylan R. (Kansas State University, 2021)
Parks and protected areas (PPA) are commonly managed as a function of visitor related impacts. Indicators of quality, and their associated thresholds help park managers make decisions in the interest of both providing optimal recreation experiences, and ecological resource protection. Given the importance of visitor thresholds in informing managerial decisions, a better understanding of how experienced conditions may influence thresholds, and what factors may moderate this relationship, is essential to successful park management. Potential moderators of this relationship include indicator type, park setting and past use history. Four unique parks were used to provide for the park setting moderation, and to provide unique indicator types. These moderators were investigated using the Hayes PROCESS macro tool. Overall, indicator type and park setting display the potential to moderate the ability for experienced conditions to predict thresholds. This implies that reported thresholds can be altered by certain moderators and this should be taken into account when formulating studies. These findings build the foundation for a deeper understanding of threshold development in recreation settings and will serve to improve how PPAs are managed for visitor use.
Keywords: Recreation; Threshold; Moderation